Operational modal analysis of an eight-storey building with asynchronous data incorporating multiple setups. (15th June 2018) - Zhu, Yi-Chen; Xie, Yan-Long; Au, Siu-Kui
Highlights: Ambient vibration test of an eight-storey building based on asynchronous data. Investigation of modal identification quality based on asynchronous data incorporating multiple setups in full-scale tests. Analysis of identification uncertainties from a Bayesian perspective. Abstract: This paper presents operational modal analysis of an eight-storey concrete building using ambient vibration data collected in an 'asynchronous' manner, i.e., different sensors using possibly different clocks for data sampling. Five force-balance accelerometers were used with a number of setups to cover all locations of interests. Modal identification is performed using a Bayesian frequency domain method for asynchronous data and the global mode shape is assembled using the global least square method. The identified modal parameters based on asynchronous data are evaluated by comparing with those identified based on synchronous data. The identification uncertainties of modal parameters are investigated through the posterior coefficient of variation in a Bayesian context. The study provides insights into the challenges encountered when using asynchronous data for operational modal analysis in a practical context.